Crocodile postmarks from around the world. - Indraneil, Das (Philatelic Society of Kuching, Sarawak, 2022)
7 June is celebrated as World Crocodile Day, to draw attention to the crocodilians (including crocodiles, alligators, caiman and the gharial) of the world. The first crocodilians to be featured on stamps (see Lever, 1985; Das, 2014) were the Saltwater Crocodile (Crocodylus porosus) from North Borneo (from the British colony corresponding to the modern-day Malaysian state of Sabah), in February 1894 (SG 76), reprinted with a slightly different design, also recess-printed within a blue frame, between March 1897–1902 (SG 106).